A Cotton Cyclin-Dependent Kinase E Confers Resistance to Verticillium dahliae Mediated by Jasmonate-Responsive Pathway - Li, Xiancai; Pei, Yakun; Sun, Yun; Liu, Nana; Wang, Ping; Liu, Di; Ge, Xiaoyang; Li, Fuguang; Hou, Yuxia (Frontiers in Plant Science, 2018)
Many subunits of the Mediator transcriptional co-activator complex are multifunctional proteins that regulate plant immunity in Arabidopsis. Cotton cyclin-dependent kinase E (GhCDKE), which is a subunit of the cotton (Gossypium hirsutum) Mediator complex, has been annotated, but the biological functions of this gene associated with regulating disease resistance have not been characterized. Here, we cloned GhCDKE from cotton and confirmed that GhCDKE belonged to the E-type CDK family in the phylogenetic tree, and, as in other eukaryotes, we found that GhCDKE interacted with C-type cyclin (GhCycC) by yeast two-hybrid and luciferase complementation imaging assays. Expression of GhCDKE in cotton was induced by Verticillium dahliae infection and MeJA treatment, and silencing of GhCDKE expression in cotton led to enhanced susceptibility to V. dahliae, while overexpression of GhCDKE in Arabidopsis thaliana enhanced resistance to this pathogen. Transgenic expression assay demonstrated that the transcriptional activity of GhPDF1.2pro:LUC in GhCDKE-silenced cotton was dramatically inhibited. In addition, the expression of jasmonic acid (JA)-regulated pathogen-responsive genes was dramatically up-regulated in GhCDKE-overexpressed plants after inoculation with V. dahliae, and the roots of GhCDKE-overexpressed A. thaliana were more susceptible to MeJA treatment. These results indicated that GhCDKE regulates resistance against V. dahliae and that this resistance is mediated by JA response pathway.